Defacement of ETICS cladding due to hygrothermal behaviour - Eva Barreira (2008)
External thermal insulation systems for walls (expanded polystyrene insulation faced with a thin rendering) ETICS have been used in Portugal since the nineties. Despite the thermal advantages, Portuguese buildings covered with ETICS are faced with a huge and yet unsolved problem: the systems defacement caused by microbiological growth. In recent years, although several studies have been carried out to solve this problem, the practical conclusions are not very satisfactory: so far the only feasible solution is to use biocides. These chemical products are not environmentally friendly and are considerably expensive because of their short-term effectiveness. To obtain a less expensive solution to this problem, it is essential to first understand the hygrothermal behaviour of façades covered with ETICS, namely, the dynamic heat exchange between the ETICS exterior layer and the atmosphere. It is also very important to study the influence of the surfaces orientation and the local climate. This paper presents the results of an experimental characterization of ETICS hygrothermal behaviour performed by the Building Physics Laboratory (LFC) of the Faculty of Engineering of Porto University (FEUP). In-situ tests are being carried out on a building covered with ETICS located in Portugals northwest region.